Pengaruh Model Pembelajaran Make A Match Berbantuan Media Flashcard Terhadap Hasil Belajar Siswa Pada Mata Pelajaran IPAS Kelas V SD Negeri 101775 Sampali - Siti Rahmayani; Yusra Nasution; Laurensia Masri Perangin Angin; Edizal Hatmi; Husna Parluhutan Tambunan (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the effect of the Make a Match learning model assisted by flashcard media on student learning outcomes in the subject of science in grade V of SD Negeri 101775 Sampali. This type of research is Quasi Experiment. The sample in this study were grade V students of SD Negeri 101775 Sampali totaling 48 students. Data collection instruments used interviews, observations, tests, and documentation. Data analysis techniques used normality tests, homogeneity tests, and hypothesis tests (t-tests). Research findings show that there is a difference in the average value between the experimental class and the control class. The average post-test value obtained from the experimental class was 83.65 and the average value of the control class was 72. Furthermore, from the results of the independent sample t-test, it was obtained that tcount> ttable, namely 5.187> 2.013 and a significance value of 0.000 <0.05 can be concluded that the hypothesis Ho is rejected and Ha is accepted. This shows that there is a significant influence of the use of the Make a Match learning model assisted by flashcard media on student learning outcomes in the science subject of class V of SD Negeri 101775 Sampali.